One of the boys - Zeller, Victoria (Hoboken : Levine Querido, 2025)
"Grace Woodhouse has left a lot behind. She used to have a great friend group, an amazing girlfriend, and a right foot set to earn her a Division I football scholarship-before she came out as trans. As senior year begins, Grace is struggling to find her place in early transition, new social circles, and a life without football. But when her skills as the best kicker in the state prove to be vital, her old teammates beg her to come out of retirement, dragging her back into a sport-into a way of life-she thought had turned its back on her forever. When a chance meeting cracks the door to college football back open, she has to decide how much of herself she's willing to give up for the game she loves"--
Ages 12-18
Stonewall Young Adult Book Award Winner, 2026
Keywords: Transgender athletes -- Juvenile fiction; Transgender people -- Juvenile fiction; Football players -- Juvenile fiction; Stonewall Book Award; Transgender people -- Fiction; Athletes -- Fiction; Football players -- Fiction; Bildungsromans; Queer fiction